Comparing Heuristic Evaluation and MALTU Model in Interaction Evaluation of Ubiquitous Systems - de Souza Filho, José Cezar; Brito, Marcos Randel Freitas; Sampaio, Andréia Libório (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Ubiquitous systems are made up of sensors and smart devices that communicate with each other to achieve certain goals. They have specific characteristics, such as transparency, attention, calmness, mobility, and context-awareness. Given that the Human-Computer Interaction (HCI) evaluation methods have been proposed for traditional systems, these characteristics present challenges that may require their adaptation. In this paper, we conducted an exploratory study aimed to compare the suitability of Heuristic Evaluation and the MALTU Model to evaluate the Usability and User eXperience (UX) of ubiquitous systems. For this, we apply both methods for evaluating a healthcare system and perform a comparative analysis. From our findings, MALTU is indicated for UX evaluation, being a low-cost approach when compared to Heuristic Evaluation, which is indicated for usability evaluation. Both methods were able to identify the problems that emerge from ubiquity and can provide better results when applied in aggregate. Furthermore, we provide recommendations to apply both methods for the Usability and UX evaluation of ubiquitous systems.